KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEMBANGUN CITRA SEKOLAH DI MI MUHAMMADIYAH TINGGARJAYA - Laelatuzzahro, Oepyt Risky; Budiyono, Alief (PREMIERE : Journal of Islamic Elementary Education, 2023)
This study aims to find out how the principal's leadership transformation in building the school's image, principles and components of transformational leadership at MI Muhammadiyah Tinggarjaya. The research method used is a qualitative method, while the data collection technique in this study uses Library Research and interviews. While the results of research on the transformational leadership of school principals in building the image of the school at MI Muhammadiyah Tinggarjaya is that the principal has a clear vision and mission for each program or innovation carried out and communicates with teachers and staff at MI Muhammadiyah Tinggarjaya in order to build good school image. The use of Instagram social media as a school branding medium with the aim of being able to build a good school image.